Nonlinear Dynamics, Volume 1 Proceedings of the 33rd IMAC, A Conference and Exposition on Structural Dynamics, 2015 - Kerschen, Gaëtan (Conference Proceedings of the Society for Experimental Mechanics Series,, 2016)
Nonlinear Dynamics, Volume 1.  Proceedings of the 33rd IMAC, A Conference and Exposition on Balancing Simulation and Testing, 2015, the first volume of ten from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Nonlinear Oscillations Nonlinear Simulation Using Harmonic Balance Nonlinear Modal Analysis Nonlinear System Identification Nonlinear Modeling & Simulation Nonlinearity in Practice Nonlinear Systems Round Robin on Nonlinear System Identification.